Emergence of a Novel Bluetongue Virus Serotype, China 2014. Issue 6 (5th September 2016) - Sun, E. C.; Huang, L. P.; Xu, Q. Y.; Wang, H. X.; Xue, X. M.; Lu, P.; Li, W. J.; Liu, W.; Bu, Z. G.; Wu, D. L.
Summary: One hundred and twenty‐six blood samples were collected from healthy sheep and goats in Xinjiang, China, during July 2014. Seventy‐three samples (57.93%) were bluetongue virus (BTV) serology‐positive, and 39 samples (30.95%) were BTV NS1 gene‐positive. BTV strain XJ1407 was isolated from the blood of BTV NS1 gene‐positive animals and sequenced. Analysis of its genome sequence suggests that XJ1407 is a novel BTV serotype.